Data from: Range-wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange, and distinct demographic histories - Statham, Mark J.; Wang, Zhenghuan; Soulsbury, Carl D.; Janecka, Jan; Sacks, Benjamin N.; Aubry, Keith B.; Berry, Oliver; Edwards, Ceiridwen J.; Murdoch, James (Dryad, 2020)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox (Vulpes vulpes), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya (SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization timeframe suggested by mtDNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y-chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long-term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva. Statham_nuclear_species_tree_800millionStatham_MrBayes_tree_12millionStatham_Beast_mtDNA_modern_only_100millionStatham_Beast_mtDNA_modern+ancient_100MStatham_Beast_Input_Nuclear_strict_800M_20131127ii*Beast input fileStatham_mtDNA_unique_haplotypes_alignmentStatham_Fox_mtDNA_datasetRed fox mtDNA dataStatham_Fox_Autosomal_Y_and_mtDNAcombinations